2012
DOI: 10.1159/000336309
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Creatinine Clearance in a Case of Necrotizing Fasciitis and Anuria

Abstract: Necrotizing fasciitis can present with concomitant acute kidney injury. The etiology of acute kidney injury is often multifactorial; potential sources include volume depletion, abdominal compartment syndrome, rhabdomyolysis, and acute tubular necrosis (which may be related to hemodynamic instability, medications, or sepsis/infection). Kidney injury, defined via changes in serum creatinine, portends increased morbidity and mortality. Thus, it is crucial to accurately diagnose and assess the severity of kidney i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The exact cause cannot be confirmed, as any number of events or pathological processes could have occurred in the interim unknown to the clinicians. Nonetheless, multiple clinicians agreed based on available documentation associating necrotizing soft-tissue infections (NSTIs) with AKI [ 14 ], the significant variation between her baseline and current RFTs, and a review of her available medical history showed a lack of other significant changes in underlying medical conditions. A review of available literature demonstrates that NSTIs are associated with AKI, due to multiple possible underlying pathological processes caused by the infection, including hypoperfusion, rhabdomyolysis, and acute tubular necrosis amongst many other listed causes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact cause cannot be confirmed, as any number of events or pathological processes could have occurred in the interim unknown to the clinicians. Nonetheless, multiple clinicians agreed based on available documentation associating necrotizing soft-tissue infections (NSTIs) with AKI [ 14 ], the significant variation between her baseline and current RFTs, and a review of her available medical history showed a lack of other significant changes in underlying medical conditions. A review of available literature demonstrates that NSTIs are associated with AKI, due to multiple possible underlying pathological processes caused by the infection, including hypoperfusion, rhabdomyolysis, and acute tubular necrosis amongst many other listed causes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, multiple clinicians agreed based on available documentation associating necrotizing soft-tissue infections (NSTIs) with AKI [ 14 ], the significant variation between her baseline and current RFTs, and a review of her available medical history showed a lack of other significant changes in underlying medical conditions. A review of available literature demonstrates that NSTIs are associated with AKI, due to multiple possible underlying pathological processes caused by the infection, including hypoperfusion, rhabdomyolysis, and acute tubular necrosis amongst many other listed causes [ 14 ]. The learning point here is simply a further case to reinforce the link between NSTIs and AKI, as well as the importance of following RFTs during the clinical course of a case of NF to prevent serious renal repercussions.…”
Section: Discussionmentioning
confidence: 99%